New Insights on Rotenone Resistance of Complex I Induced by the m.11778G>A/MT-ND4 Mutation Associated with Leber’s Hereditary Optic Neuropathy - Francesco Musiani; Laura Rigobello; Luisa Iommarini; Valerio Carelli; Mauro Degli Esposti; Anna Maria Ghelli (Molecules, 2022)
The finding that the most common mitochondrial DNA mutation m.11778G>A/MT-ND4 (p.R340H) associated with Leber’s hereditary optic neuropathy (LHON) induces rotenone resistance has produced a long-standing debate, because it contrasts structural evidence showing that the ND4 subunit is far away from the quinone-reaction site in complex I, where rotenone acts. However, recent cryo-electron microscopy data revealed that rotenone also binds to the ND4 subunit. We investigated the possible structural modifications induced by the LHON mutation and found that its amino acid replacement would disrupt a possible hydrogen bond between native R340 and Q139 in ND4, thereby destabilizing rotenone binding. Our analysis thus explains rotenone resistance in LHON patients as a biochemical signature of its pathogenic effect on complex I.